Pre-service teachers' self efficacy towards teaching thinking skills and their critical thinking disposition : a case study in the Maldivian National University, Maldives - Fareeda, Fathimath (Institute of Education, International Islamic University Malaysia, 2013)
This study examined pre-service teachers' self-efficacy towards teaching thinking skills and their critical thinking disposition. This is a quantitative study conducted in Maldivian National University involving seventy four pre-service teachers. The respondent comprised of 56 female and 18 male pre-service teachers. The self-efficacy towards teaching thinking skills were measured using a questionnaire which was devised by Tebbs (2000) and their critical thinking disposition were measured using a questionnaire which was devised by Irani, Rudd, Gallo, Ricketts, Friedel, & Rhoades (2007). In addition, associated demographic data were obtained included gender, age, GPA and the type of teacher education program of the pre-service teachers of Maldivian National University. The questionnaire which measured self-efficacy towards teaching thinking skills consisted of four subscales; Creating a Classroom Fit to Think, Teaching Higher Order Thinking Skills, Teaching for Transfer and Recognise How Students Think. The questionnaire which measured critical thinking disposition consisted of three subscales; Engagement, Maturity and Innovativeness. The findings of this study revealed that the pre-service teachers had an average level of self-efficacy towards teaching thinking skills and a high level of critical thinking disposition. The pre-service teachers had the lowest self-efficacy in Recognizing How Students Think and most confident in Creating a Classroom Fit to Think. In all of the domains in critical thinking disposition the pre-service teachers at MNU had a high level of critical thinking disposition. Furthermore, study also showed that there was no difference in gender, age or GPA in the pre-service teachers' self-efficacy towards teaching thinking skills and their critical thinking disposition. While there was no significant difference in the pre-service teachers' self-efficacy towards teaching thinking skills and the program the pre-service teachers were enrolled in, there was a significant difference in the pre-service teachers' critical thinking disposition and the type program the pre-service teachers were enrolled in. There was no significant relationship between the pre-service teachers' self-efficacy towards teaching thinking skills and their critical thinking disposition with any of the demographic variables. A positive correlation between the pre-service teachers' self-efficacy towards teaching thinking skills and their critical thinking disposition was found.